An introduction to metamaterials and waves in composites - Banerjee, Biswajit, 1967- (CRC Press/Taylor & Francis Group, 2011)
Elastodynamics, Acoustics, and Electrodynamics A note about notation Elastodynamics Acoustics ElectrodynamicsPlane Waves and Interfaces Plane wave solutions Plane wave solutions in elastodynamicsPlane wave solutions in acoustics Plane wave solutions in electrodynamics Wave propagation through a slabSources and Scattering Plane wave expansion of sources Single scattering from spheres Multiple scatteringElectrodynamic Metamaterials A model for the permittivity of a medium Negative permittivity materials Artificial magnetic metamaterials Negative refraction and perfect lensesAcoustic and Elastodynamic Metamaterials Dynamic mass densityFrequency-dependent moment of inertia Negative elastic moduli Band gaps, negative index and lenses Anisotropic density Willis materials in elastodynamics A Milton-Willis model material Extremal materialsTransformation-Based Methods and CloakingTransformations Cloaking of electrical conductivity Cloaking for electromagnetism Inertial acoustic cloaking Transformation-based cloaking in elastodynamics Acoustic metafluids and pentamode materialsWaves in Periodic MediaPeriodic media and the Bloch condition Elastodynamics in the quasistatic limit Electromagnetic waves in the quasistatic limitBand gap phenomena in periodic compositesWaves in Layered MediaWave equations in layered media Piecewise-constant multilayered media Smoothly varying layered media Propagator matrix approach Periodic layered media Quasistatic homogenization of layered mediaEpilogueReferences Index.